Magnetic and thermodynamic studies on the distorted kagome magnet Pr3⁡BWO9 - Elghandour, Ahmed; Arneth, Jan Victor; Yadav, A.; Luther, S.; Khuntia, P.; Klingeler, Rüdiger (Physical review, 2025)
We report specific heat, ac/dc magnetic susceptibility as well as static and pulsed field magnetization studies on the distorted kagome magnet Pr3⁡BWO9 down to 0.4 K and up to high magnetic fields. The low-temperature thermodynamic properties are found to be governed by an electronic quasidoublet ground state, the energy splitting of which amounts to Δ1≃18 K and exhibits a quadratic field dependence with 𝑔eff=2.6. Fitting of the specific heat data implies that the next excited state is strongly gapped at Δ2=430 K and threefold degenerate in zero field. Our dc and ac susceptibility studies down to 0.4 K do not detect signatures of distinct spin glass behavior. Pulsed field magnetization measurements up to 60 T confirm the Ising-like paramagnetic nature of the magnetic ground state, which is characterized by 𝑚𝐽=±4 and the anisotropy energy 𝐸𝑎≃950 K.
Im Titel erscheinen die Zahlen tiefgestellt
Gesehen am 04.12.2025